2019
DOI: 10.9755/ejfa.2019.v31.i10.2019
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring industrial hydrogenation of soybean oil using self-organizing maps

Abstract: Monitoring the hydrogenation reaction is crucial to guarantee a product with desired properties. The combination of gas chromatography (GC) with self-organizing maps (SOM) may be an alternative to extract relevant information during the hydrogenation. We analyzed two partially hydrogenated fats produced in an industrial reactor. The quantification of the fatty acids methyl esters and the iodine value (IV) calculation was performed by GC. The SOM was able to cluster the samples according to the IV and reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Earlier, several authors reported SOM for describing the features of food materials particularly in the field of sensory analysis. Sanchez et al, 2019 andMilovanovic et al, 2019 had studied the hydrogenation of soybean oil and the classification of different wine products based on organic acid respectively. [36][37]3] Though it is the first kind of approach, in terms of classification by food compositional analysis, sensory attributes and physical characterization like textural and color analysis through SOM.…”
Section: 𝑊 = 𝛽𝑦 − 𝛾𝑊[𝑊 𝑈 𝑦]mentioning
confidence: 99%
“…Earlier, several authors reported SOM for describing the features of food materials particularly in the field of sensory analysis. Sanchez et al, 2019 andMilovanovic et al, 2019 had studied the hydrogenation of soybean oil and the classification of different wine products based on organic acid respectively. [36][37]3] Though it is the first kind of approach, in terms of classification by food compositional analysis, sensory attributes and physical characterization like textural and color analysis through SOM.…”
Section: 𝑊 = 𝛽𝑦 − 𝛾𝑊[𝑊 𝑈 𝑦]mentioning
confidence: 99%
“…It is also possible to visualize the results by the weight maps or weight plan through a level contour graph, representing each variable’s influence for the sample segmentation. Together with the topological map, they observe behavior rules for each group formed and infer each variable’s influence on the result obtained [ 25 ]. For the weight maps build, the w j values for each variable were interpolated by “nearest” and “spline” functions (in Matlab) to regularize the hexagonal grid, using the automatic arrangement of the samples obtained from the topological map.…”
Section: Methodsmentioning
confidence: 99%
“…SOM has already been used successfully for data mining in several areas of knowledge [24,[26][27][28][29][30], like food science [26,28,29], fuels [27], monitoring chemical reactions [24,30], and other applications [25,31,32]. Recently, SOM was used to verify the spatial relationship of the COVID-19 spread in countries and states in Mexico [31].…”
Section: Of 16mentioning
confidence: 99%